Gestão de resíduos sólidos de serviço de saúde : estudo comparativos em unidade hospitalares de Aracaju/se - Cunha, Grasiela Freire da (2013)
The object of this research was to analyze the waste management of health services in hospitals located in the city of Aracaju/SE. Specifically, sought to describe the procedures for segregation, packaging, collection, storage, transportation, treatment and final disposal of the solid waste management, analyze the degree of officials knowledge of the hospitals on the management of such wastes and perform comparative analysis of management practices in hospitals RSS, verifying their compliance with Resolution No. 306/2004 of ANVISA. This is a descriptive and exploratory study, whose research strategy adopted was multiple case study. Data collection was conducted through semi-structured questionnaire application, on-site observation, with the help of script and document analysis. The research population consisted of 285 professionals from the clinical staff (doctors, nurses, technicians and nursing assistants) and hygienist of the three hospitals studied, defined by non-probability sampling by quotas. Data were analyzed with SPSS software, content analysis and triangulation of data. It was found that all healthcare facilities searched showed problems related to inadequate segregation of waste. The three hospitals surveyed have the same procedures with respect to segregation, packing, collection, storage, transportation, treatment and final disposal of the solid waste management. In two establishments, the locations used for external storage of waste do not meet current standards. Private hospitals had the solid waste management plan duly updated and structured and seek to meet current standards and their applicability correct. It was noted, however, that the respondents, in all hospitals, have low level of knowledge about issues related to the management of solid waste management held by health facilities. In general, it was found that establishments assessed implement a policy requiring training, using attractive and efficient mechanisms for training of professionals involved in the management of solid waste management.